Pengaruh Kesadaran Wajib Pajak Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM Pada KPP Pratama Cimahi - Meliyanti, Wina; Mulyana, Asep; Sutrisna, Wawan Asad; Munawar, Hendrik Sudria; Amperawati, Susani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the extent of the influence of taxpayer awareness and tax knowledge on the compliance of MSME taxpyers at the Cimahi Tax Service Office. This research employs a quantitative descriptive method with a multiple linear regression analysis model. Data was collected by distributing questionnaires directly to 100 respondents. The results indicate that, partially, both taxpayer awareness and tax knowledge positively and significantly influence MSME taxpayer compliance. Simultaneously, taxpayer awareness and tax knowledge positively and significantly influence MSME taxpayer compliance.